On merging of resonant periodic orbits 4:3; 3:2 and 2:1 in Sun-Jupiter photo gravitational restricted three-body problem - Kumar, Prashant; Krishan Sharma, Ram (International Journal of Advanced Astronomy, 2019)
We explore the merging of resonant periodic orbits in the frame work of planar circular restricted three body problem with the help of PoincarÃ© surface of section. We have studied the effect of solar radiation pressure on 4:3, 3:2 and 2:1 periodic orbits. It is found that radiation pressure helps in merging these orbits (4:3 and 3.2 into 1:1 resonance and 2:1 into 1:1 resonance). At the time of merging these orbits become near-circular. The period and size of these orbits reduce with the increase in radiation pressure.Â Â